Effect of Changes in Artificial Turf on Sports Injuries in Male University Soccer Players - Fujitaka, Kohei (Orthop J Sports Med, 2017)
BACKGROUND: Studies comparing the types and severity of trauma and injuries caused by different types of field surfaces have been conducted. However, there have been no studies on sports injuries caused by temporal deterioration of long-pile artificial turf fields and related decreases in the rubber chip and silica sand infill. PURPOSE: To investigate the influence of an artificial turf field on sports injuries in a university soccer team. STUDY DESIGN: Descriptive epidemiological study. METHODS: A total of 397 male soccer players who were members of a single university soccer team were surveyed over a 12-year period, from April 2003 to March 2015. During this period, the team played for 4 years on a soil field (2003-2006) and 8 years on artificial turf (2007-2014). We analyzed the effect of changes in the artificial turf on the incidence rate of sports injuries (injury rate per 1000 athlete-exposures). We calculated the incidence rate of injuries sustained by the team and compared the results for each year of the study. RESULTS: After conversion of the field to artificial turf, there was a significant increase in the incidence of upper extremity trauma (P < .05). There was a significant increase in lower extremity sprains from 2007 to 2008, 1 year after the conversion from soil to artificial turf (P < .05). Analysis of the incidence of lower extremity muscle strain indicated that although the injury rate increased progressively, it decreased significantly after the insertion of additional rubber chips in 2014 (P < .05). CONCLUSION: After conversion to artificial turf, there was a significant increase in the incidence of upper extremity trauma. After the refurbishing with additional rubber chips, the incidence of lower extremity muscle strain significantly declined. When analyzing measures that could prevent sports injuries related to soccer, it is necessary to take into consideration the changes that occur to the artificial turf over time.